Solid-Liquid Phase Equilibria of the Quaternary System NaCl + NH4Cl + NaHCO3 + NH4HCO3 + H2O at 283.15 and 313.15 K - Shuangshuang Gu; Haoran Li; Kangrui Sun; Yafei Guo; Tianlong Deng; Lingzong Meng (Journal of Chemistry)
The solid-liquid phase equilibria for the quaternary system (NaCl + NH4Cl + NaHCO3 + NH4HCO3 + H2O) at 283.15 and 313.15 K were studied with the isothermal solution method. There are four crystallization regions corresponding to NaCl, NH4Cl, NaHCO3, and NH4HCO3, five univariant solubility curves, and two invariant points saturated with the three coexisting minerals in the phase diagrams at the two temperatures. A comparison of the phase diagrams at 283.15 and 313.15 K shows that the areas of regions for NaCl, NaHCO3, and NH4Cl increase obviously. In contrast, the area of NH4HCO3 region decreases significantly as the temperature rises. The density and refractive index in the quaternary system change regularly with the concentration changing. The calculated densities and refractive indices in the quaternary system at the two temperatures with the empirical equations agree well with the experimental values.